Analysis of Water Loss in the District of Meter Area (DMA) Bumi Kepongongan Indah Regency, Cirebon for Civilization - Safitri, Adam; Wahyudi, Slamet Imam; Soedarsono, Soedarsono; Yunus, Mahmud; Carsono, Nono; Amaliah, Lia (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Based on the calculation of Non-Revenue Water/Un-billed Water (NRW/ATR), it is known that the value of NRW (Non-Revenue Water/Unbilled Water) in the Meter Area (DMA) District of Perum Bumi Kepongpongan Indah, Cirebon Regency with 204 SR subscribers, in February 2020 was relatively high, at 50.92%. The purpose of this study was to determine the level of water loss by looking for causes arising from water leaks, knowing the location of water loss both physically and non-physically, and knowing how to control Non-Revenue Water (NRW) water loss. The methodology used is to collect secondary data and primary data. Secondary data were obtained from the Cirebon City Water Supply Corporation, including images of the DMA distribution network and monthly customer water usage data taken from February to April 2020. Primary data was obtained by means of surveys and direct field observations by testing the steptest in one test. DMA. The result of controlling and decreasing NRW/ATR is that it can reduce the value of NRW/ATR from 50.92% in June 2020 down to 46% based on (WB 0) and in August 2020 down to 25% based on the results of simultaneous readings (WB 1). Pressure also needs to be considered, because pressure that is too high can also increase water loss. So that the Pressure Reducing Valve (PRV) is installed which can reduce excess pressure, from the PRV installation reducing the water loss rate from 25% in August 2020 to 20% in February 2021.